Using restorative circles in schools : how to build strong learning communities and foster student wellbeing - Follestad, Berit, 1947-; Wroldsen, Nina, 1959-; Hopkins, Belinda, 1956- (London ; Philadelphia : Jessica Kingsley Publishers, 2019)
Restorative circles are an effective way of implementing restorative justice, through starting a conversation wider than just the victim and the offender. Proven to be an effective way of healing and building relationships, tackling bullying within schools and providing a sense of community, this book gives everything needed for a school to start implementing restorative circles. Accompanied by illustrations, interviews and case studies to show how to start using restorative circles, this practical guide is the perfect introduction for schools looking to improve their methods of conflict resolution.
Introduction -- Restorative circles : a mindset, a method and tool for conflict resolution -- Implementing the circle method -- Restoring relations -- Games and activities.
Originally published in Norwegian in 2017 by Fagbokforlaget.
"This edition has been updated with new material"--Page 8
"Translation of original material undertaken by Nina Wroldsen"--Page 8
Includes bibliographical references (pages 111-114) and index.
Online resource; title from PDF title page (EBSCO, Nov. 28, 2018).
eBooks on EBSCOhost
Keywords: School discipline; Restorative justice; Interpersonal relations -- Study and teaching -- Activity programs; Discipline scolaire; Justice réparatrice.; EDUCATION -- Administration -- General; EDUCATION -- Organizations & Institutions; Interpersonal relations -- Study and teaching -- Activity programs; Restorative justice; School discipline